2020
DOI: 10.1136/oemed-2019-106253
|View full text |Cite
|
Sign up to set email alerts
|

Educational differences in the influence of health on early work exit among older workers

Abstract: ObjectivesPrevious research has shown that poor physical and mental health are important risk factors for early work exit. We examined potential differences in this association in older workers (50+) across educational levels.MethodsCoordinated analyses were carried out in longitudinal data sets from four European countries: the Netherlands (Longitudinal Aging Study Amsterdam), Denmark (Danish Longitudinal Study of Ageing), England (English Longitudinal Study of Ageing) and Germany (German Ageing Survey). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
(48 reference statements)
3
15
1
Order By: Relevance
“…In our study, higher education has a strong positive association with inability to work fulltime compared to lower and middle educational level. This seems to be in contrast with findings from other studies describing that higher educated workers are better able to adjust their work and are less work disabled than lower educated workers who are considered to be more vulnerable, have more health problems and worse working conditions [ 43 45 ]. In search for explanations for this difference, we explored if the higher educated workers in our study sample had more often diseases related with higher odds for inability to work fulltime, however this was not the case (data not shown).…”
Section: Discussioncontrasting
confidence: 88%
“…In our study, higher education has a strong positive association with inability to work fulltime compared to lower and middle educational level. This seems to be in contrast with findings from other studies describing that higher educated workers are better able to adjust their work and are less work disabled than lower educated workers who are considered to be more vulnerable, have more health problems and worse working conditions [ 43 45 ]. In search for explanations for this difference, we explored if the higher educated workers in our study sample had more often diseases related with higher odds for inability to work fulltime, however this was not the case (data not shown).…”
Section: Discussioncontrasting
confidence: 88%
“…Another study combining data from SHARE and ELSA estimated an overall prevalence of depressive symptoms of 14% among workers 50-64 years (Siegrist et al, 2012), similar to that observed in a Swedish study (Nyberg et al, 2019). However, lower prevalences of depression, more similar to what we found, have been observed in other studies among ageing workers (De Breij et al, 2020;Leijten et al, 2015;Mezuk et al, 2011). Anyway the variability in mental disorders prevalences in different countries was expected, as diagnosis and treatment of common mental disorders (i.e.…”
Section: Healthsupporting
confidence: 90%
“…This is in line with findings from a Dutch study conducted by van den Berg et al (47). Recent findings by de Breij et al (18) confirm this for Denmark when analyzing prospective data but not for The Netherlands and England, where the effects of functional limitations on disability pension were strongest. With respect to early retirement, only self-perceived health was a significant predictor in the meta-analysis (7).…”
Section: Relevance Of the Health Concept Usedmentioning
confidence: 92%
“…De Wind et al (17) found support for the hypothesis that ability and opportunity to work mediate the relation between health and early retirement. De Breij et al (18) showed that in some countries health effects on early work exit were stronger in the lower educated. This is in line with…”
Section: Two Illustrations Of Work-retirement Framework and Their Con...mentioning
confidence: 99%
See 1 more Smart Citation